Usefulness of Gd-DTPA contrast-enhanced dynamic MRI and serum determination of LDH and its isozymes in the differential diagnosis of leiomyosarcoma from degenerated leiomyoma of the uterus. Issue 4 (1st July 2002) - Goto, A.; Takeuchi, S.; Sugimura, K.; Maruo, T.
Abstract : This prospective study was conducted to identify the magnetic resonance imaging (MRI) characteristics of uterine leiomyosarcoma (LMS) and to evaluate the diagnostic accuracy of conventional MRI and dynamic MRI with or without serum measurement of lactate dehydrogenase (LDH) levels. Two hundred ninety-eight consecutive patients were entered in this study. In eligible 227 patients, ten patients with LMS and 130 patients with uterine degenerated leiomyoma (DLM) were included for the present study. Precontrast T1, T2 weighted images were obtained in all patients. Serum LDH and its isozymes were also measured. Dynamic MRI by Gd-DTPA was obtained in all patients with LMS and 32 patients with DLM in whom elevated LDH levels were observed. The contrast enhancement at 60 s after administration of Gd-DTPA was detected in all LMS, but absent in 28 of 32 DLM patients. Concerning serum LDH isozymes, both total LDH and LDH isozyme type 3 were elevated in all 10 patients with LMS. The sensitivity for determination of LMS with MRI alone, dynamic MRI alone, and combined use of MRI (including dynamic MRI) and serum LDH levels was 100% in each group. The specificity, positive predictive value, negative predictive value, and diagnostic accuracy were 93.1%, 52.6%, 100%, and 93.1% with MRI alone, and 93.8%, 83.3%, 100%, and 95.2% with dynamic MRI alone, and 100%, 100%, 100%, 100% with combined use of LDH and MRI, respectively. In conclusion, the combined use of dynamic MRI and serum measurement of LDH (isozymes) seems to be useful in making a differentiated diagnosis of LMS from DLM before treatment.